A municipal waterworks building - Harris, Frank C. (My University, 1908)
Introduction: Specifications for the Erection and completion of a municipal Pumping Station to be erected at [blank], [blank], for the city of [blank], [blank], according to drawings prepared by, Frank G. Harris, Architect. This contract provides for the furnishing of all material and labor necessary for the erection and completion of the building in the time specified.
Citation: Harris, Frank C. A municipal waterworks building. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Architecture; Blueprints; Water; Graduating theses; Senior theses; Theses